Identification of iron and heme utilization genes in Aeromonas and their role in the colonization of the leech digestive tract - Maltz, Michele; Levarge, Barbara L.; Graf, Joerg (Frontiers in Microbiology, 2015)
It is known that many pathogens produce high-affinity iron uptake systems like siderophores and/or proteins for utilizing iron bound to heme-containing molecules, which facilitate iron-acquisition inside a host. In mutualistic digestive-tract associations, iron uptake systems have not been as well studied. We investigated the importance of two iron utilization systems within the beneficial digestive-tract association Aeromonas veronii and the medicinal leech, Hirudo verbana. Siderophores were detected in A. veronii using chrome azurol S. Using a mini Tn5, a transposon insertion in viuB generated a mutant unable to utilize iron using siderophores. The A. veronii genome was then searched for genes potentially involved in iron utilization bound to heme-containing molecules. A putative outer membrane heme receptor (hgpB) was identified with a transcriptional activator, termed hgpR, downstream. The hgpB gene was interrupted with an antibiotic resistance cassette in both the parent strain and the viuB mutant, yielding an hgpB mutant and a mutant with both iron uptake systems inactivated. In vitro assays indicated that hgpB is involved in utilizing iron bound to heme and that both iron utilization systems are important for A. veronii to grow in blood. In vivo colonization assays revealed that the ability to acquire iron from heme-containing molecules is critical for A. veronii to colonize the leech gut. Since iron and specifically heme utilization is important in this mutualistic relationship and has a potential role in virulence factor of other organisms, genomes from different Aeromonas strains (both clinical and environmental) were queried with iron utilization genes of A. veronii. This analysis revealed that in contrast to the siderophore utilization genes heme utilization genes are widely distributed among aeromonads. The importance of heme utilization in the colonization of the leech further confirms that symbiotic and pathogenic relationships possess similar mechanisms for interacting with animal hosts.